Exploiting the roles of nitrogen sources for HEA increment in Cordyceps cicadae - Zhu, Kexin; Ruan, Haihua; Wu, Tao; Zhang, Hongyang; Han, Wenying; Shen, Qiqing (Frontiers in Microbiology, 2024)
Cordyceps cicadae, as a new food ingredient, is a valuable edible and medicinal fungi. However, its resources are severely depleted due to environmental limitations and excessive harvesting practices. N 6 -(2-hydroxyethyl) adenosine (HEA), as an important product of Cordyceps cicadae, has the potential to be used in medical industry due to its diverse disease curing potential. However, the disclosure of HEA synthesis still severely limited its application until now. In this study, the kinetic curves for adenosine and HEA under shaker fermentation were explored. The kinetics of HEA and adenosine production exhibited a competitive pattern, implicating a possibility of sharing a same step during their synthesis. Due to HEA as a derivative of nitrogen metabolism, the effect of different nitrogen sources (peptone, yeast extract, ammonium sulfate, diammonium oxalate monohydrate, ammonium citrate dibasic, ammonium citrate tribasic) on HEA production in Cordyceps cicadae strain AH 10-4 had been explored under different incubation conditions (shaker fermentation, stationary fermentation, submerged fermentation). Our results indicated that the complex organic nitrogen sources were found to improve the accumulation of HEA content under shaker fermentation. In contrast, the optimal nitrogen source for the accumulation of HEA under stationary fermentation and submerged fermentation was ammonium citrate tribasic. But submerged fermentation obviously shortened the incubation time and had a comparable capacity of HEA accumulation by 2.578 mg/g compared with stationary fermentation of 2.535 mg/g, implicating a possibility of scaled-up production of HEA in industry by submerged fermentation. Based on the dramatic HEA production by ammonium sulphate as nitrogen resources under stationary and shaker fermentations, alanine, aspartate and glutamate as well as arginine metabolic pathway were related to the production of HEA by comparative transcriptome. Further investigation indicated that glutamic acid, which is an analog of Asp, showed an optimum production of HEA in comparison with other amino acids.